2022
DOI: 10.1186/s13014-022-02034-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of possible interobserver variability in CBCT-based soft-tissue matching using TCP/NTCP models for prostate cancer radiotherapy

Abstract: Background Prostate alignment is subject to interobserver variability in cone-beam CT (CBCT)-based soft-tissue matching. This study aims to analyze the impact of possible interobserver variability in CBCT-based soft-tissue matching for prostate cancer radiotherapy. Methods Retrospective data, consisting of 156 CBCT images from twelve prostate cancer patients with elective nodal irradiation were analyzed in this study. To simulate possible interobse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…With respect to rotation, the standard deviation exceeded 3° for 6% of the entire dataset, regardless of the axis. This study also observed inter‐observer variability, consistent with findings from previous studies 3,8,9,17–19 . These findings emphasize the need for auto‐matching techniques to minimize inter‐observer variability and achieve consistent soft‐tissue matching.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…With respect to rotation, the standard deviation exceeded 3° for 6% of the entire dataset, regardless of the axis. This study also observed inter‐observer variability, consistent with findings from previous studies 3,8,9,17–19 . These findings emphasize the need for auto‐matching techniques to minimize inter‐observer variability and achieve consistent soft‐tissue matching.…”
Section: Discussionsupporting
confidence: 90%
“…This study also observed inter-observer variability, consistent with findings from previous studies. 3,8,9,[17][18][19] These findings emphasize the need for auto-matching techniques to minimize inter-observer variability and achieve consistent soft-tissue matching.…”
Section: Inter-observer Variabilitymentioning
confidence: 78%
See 3 more Smart Citations